2021
DOI: 10.1111/jch.14375
|View full text |Cite
|
Sign up to set email alerts
|

Treatment and control of modifiable cardiovascular risk factors among patients with diabetes mellitus and hypertension in Inner Mongolia: A cross‐sectional study

Abstract: The authors assessed treatment and control of blood glucose, blood pressure (BP), and blood lipids among patients from Inner Mongolia with diabetes mellitus (DM) and hypertension (HTN) and identified the modifiable factors associated with treatment and achievement of blood glucose, BP, and blood lipid targets. The authors used a multistage stratified cluster sampling method according to geographical location and level of economic development in Inner Mongolia. Among patients with DM and HTN, the crude rates of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
0
2
Order By: Relevance
“…So far, however, there has been little discussion about the FPG control rate in comorbid patients. Bi et al 44 found that 5.13% of hypertensive patients with diabetes achieved the FPG control goal in Inner Mongolia, which was much lower than the control rate in this study. This discrepancy could be attributed to the fact that the patients in this study had better adherence to medication and life interventions due to follow-up, the baseline FPG of the patients was lower in this study, the stricter FPG control goal of Bi’s study, and regional and demographic differences.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…So far, however, there has been little discussion about the FPG control rate in comorbid patients. Bi et al 44 found that 5.13% of hypertensive patients with diabetes achieved the FPG control goal in Inner Mongolia, which was much lower than the control rate in this study. This discrepancy could be attributed to the fact that the patients in this study had better adherence to medication and life interventions due to follow-up, the baseline FPG of the patients was lower in this study, the stricter FPG control goal of Bi’s study, and regional and demographic differences.…”
Section: Discussioncontrasting
confidence: 80%
“…So far, however, there has been little discussion about the FPG control rate in comorbid patients. Bi et al 44 found that 5.13% of hypertensive patients with diabetes achieved the FPG control goal in Inner Mongolia, which was much lower than the control rate in this study. This…”
contrasting
confidence: 80%